2022
DOI: 10.3389/fpsyg.2022.881603
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Death-Anxiety-Induced Fear of COVID-19 in Compliance With and Acceptance of Government-Issued COVID-19 Regulations

Abstract: The present research was conducted to empirically examine whether death anxiety is the fundamental fear that feeds people’s fear of COVID-19 and leads to increased behavioral compliance with and acceptance of COVID-19 regulations. Results from an online survey of 313 participants from New York City show that death anxiety was, indeed, positively associated with behavioral compliance with, but not acceptance of, COVID-19 regulations via an increased fear of COVID-19. Hence, media campaigns that are designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Social isolation and limited physical activity, on the other hand, was considered to protect residents from being infected. Some researchers found that death anxiety was positively associated with behavioral compliance with unprecedented restrictions [ 50 ]. Therefore, it may be explained that Chinese residents accepted quarantine strategies to cope with the spread of the virus at the cost of losing strong and weak ties.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation and limited physical activity, on the other hand, was considered to protect residents from being infected. Some researchers found that death anxiety was positively associated with behavioral compliance with unprecedented restrictions [ 50 ]. Therefore, it may be explained that Chinese residents accepted quarantine strategies to cope with the spread of the virus at the cost of losing strong and weak ties.…”
Section: Discussionmentioning
confidence: 99%
“…Also, one interesting perspective was analyzed by Kehr et al (19). The authors empirically examine the relation between the behavioral compliance and acceptance of COVID-19 regulations imposed by local authorities in New York and psychologically features of the individuals (like death anxiety).…”
Section: Literature Reviewmentioning
confidence: 99%